Synthesis and post-polymerization functionalization of a tosylated hyper-crosslinked polymer for fast and efficient removal of organic pollutants in water - Todee B. (2023)
The synthesis and post-synthetic modification of a novel tosylate-functionalized hyper-crosslinked polymer (HCP) for the purpose of water remediation are reported. An FeCl3-catalyzed cross-linking reaction of a bis-tosylated arene monomer (M-OTs) gave a tosylate-substituted HCP precursor (P-OTs) in high yield. In contrast to halogenated monomers, the tosylate functional groups in M-OTs are inert under such polymerization conditions, allowing for facile chemical modification of P-OTsvia SN2, reduction, and oxidation reactions to afford a series of HCPs containing thioacetate (P-SAc), thiol (P-SH), and sulfonic acid (P-SO3H) functional groups. Characterized using a suite of techniques including FT-IR, elemental analysis, TGA, SEM, and BET, the sulfur-containing HCP series were investigated as organic pollutant extractant materials for contaminated water streams. Wherein it was demonstrated that the HCP series exhibited highly selective adsorption towards cationic species in aqueous solution operating in a considerable pH window and artificial sea and fresh water. Importantly, by virtue of strong electrostatic interactions, P-SO3H outperformed other HCPs in rapid and efficient methylene blue (MB) and paraquat (PQ) adsorption with impressive adsorption capacities (qmax) of 582.60 mg g−1 and 568.13 mg g−1, respectively.